Study of twistronics induced superconductivity in twisted bilayer graphene - Paudel, Rajendra; Upadhya Dhakal, Nabin; Pantha, Nurapati (BIBECHANA, 2026)
This work investigates the electronic properties of twisted bilayer graphene (TBG) through computational calculations, with the aim of understanding the emergence of flat bands and conditions favorable for superconductivity close to the magic angle. This study utilizes  continuum model and the low-energy Hamiltonians were derived from angle-dependent datasets provided by Carr et al. Using this model, band structure, density of states (DoS), and Fermi velocity were systematically calculated across a range of twist angles. The calculations were performed by discretizing high-symmetry paths in the moiré Brillouin zone for band structure calculations, uniformly sampled using square grid size for DoS analysis, and employing finite difference methods to evaluate Fermi velocity near the Dirac points. The results identify a narrow magic angle window around , where bands become nearly dispersionless, the DoS exhibits a sharp peak, and the Fermi velocity is strongly suppressed. This computational framework does not directly predict superconductivity but rather establish the electronic foundation for exploring the flat-band physics and correlation-driven phenomena like unconventional superconductivity in Twisted Bilayer Graphene.